Consumer Protection for Scarcity of Hospital Beds the Impact of Covid in the Perspective of the Law on Hospitals - Mawaddah Safira; Inosentius Samsul (Universitas Kuningan, 2021)
Getting access to health care is every citizen’s right. Particularly, during the pandemic of covid-19, all hospitals must be prepared in providing community services, hospital beds included. The study aims to reveal legal protection and conduct an in-depth analysis on consumer rights and violations of hospital obligation–business actors for hospital beds scarcity due to Covid-19. The study employed normative-juridical methods. The researchers conducted a study to analyze both laws written in books. Based on this method, the researchers have to manage a logical assessment of relevant legal provisions, the implementation of consumer protection. Specifically, this should be based on Law No. 8 of 1999 on consumer protection juncto law No. 44 of 2009 on hospitals. As a matter of fact, the study found hospital beds scarcity due to the increased number of covid-19, makes the responsible hospitals and government seem unresponsive. Even though, the citizens’ rights as consumers are clearly stated in Law Number 8 of 1999 on Consumer Protection juncto Law no. 44 of 2009 on Hospitals. The follow-up actions of the authorized agency in overcoming the losses of community members are referred to the applicable laws and regulations.